If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 3x + 17 Reorder the terms: y = 17 + 3x Solving y = 17 + 3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 17 + 3x
| 186=2l+2w | | 6c^3-4c= | | 30=-5(6n+g) | | 47+8y+8=180 | | (2y+1)(6-y)=0 | | 0=2x^2-12x+9 | | 2(-81+-9u+9u^2+u^3)=0 | | 8a-25=4a+3 | | 6m+3-8m+4m=-7 | | w+w+2w+14+2w+14=60 | | -2x^2+7x+3=0 | | 5x+12x=200 | | 36x^2+60x+25= | | 6x-4d=25 | | 5x-49=-2x | | 3(6x+1)=-10+5(2x+1) | | .0000852x^2-.0122x+.0514=0 | | 3(2x-5)=3-4(x+2) | | 3m+5=3-5m | | -x^2+14x-13= | | -7x-12=-9 | | 2x+5+3x=25 | | 28x^2-3x-1=0 | | 49x^2+70x+25= | | 2t^5-14t^4+20t^3= | | 2t^5-14t^4+20t^4= | | x^2+10x-224=0 | | (x-4)(x+9)=0 | | (2u+18)(u^2-9)=0 | | 2.5x+0.25x=1.25+x | | x^5-11x^4-26x^3= | | 4x-7=8+2x |